Team up - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Some of you will already know the story about the four people named Everybody, Somebody, Anybody and Nobody, but it is so illustrative of the need for this super new book that it is worth telling again.